TITLE: An informative study of data migration between repositories utilising JSON, OAI-PMH/ORE and Dublin Core/RIOXX metadata standards (Everything Version) - CREATORS_FN: Green, CREATORS_GN: Jonathan; CREATORS_FN: Price, CREATORS_GN: Vicky; CREATORS_FN: Sperring, CREATORS_GN: Dan; CREATORS_FN: Houghton, CREATORS_GN: Lee; Katie (Macmillan Publishers Limited, 2018)
ABSTRACT: This is a test record for the purposes of analysis of collected meta against particular input fieldname titles and how it is exposed through JSON export from eprints (Everything Version)